Development of wader-fish (Rasbora argyrotaenia) and kidney beans as a supplementary food: A source of protein and minerals for toddlers aged 12-24 months - Palupi Eny; Isni Oktaviani Rachmalia; Purnaningsih Ninuk; Saraswati Yudhistira; Eka Putri Wahyu; Chandra Iwansyah Ade (BIO Web of Conferences)
Protein and mineral deficiencies can also contribute to stunting. Introducing wader-fish, an underutilized-ingredient rich in protein and minerals, for the development of supplementary-food could offer a nutritious option for toddlers. This study developed a supplementary food made from wader-fish and kidney beans for toddlers aged 12–24 months, using a traditional Indonesian steamed-dish technique called pepes. Different formulations of wader-fish and kidney-beans (50:50, 70:30, and 90:10) were used to develop supplementary food. The pepes-technique, an Indonesian steamed-dish wrapped with banana leaves, was chosen to preserve nutrients and offer convenient single-serving use. Kidney beans were selected as protein complementors. The ratio of 70:30 was chosen as the optimal formula. One serving (125 g) contained 23.3% energy, 81.35% protein, 86.80% calcium, 74.82% iron, and 102.08% zinc.